The Number, Size, and Distribution of Farms, Smallholder Farms, and Family Farms Worldwide - Lowder, Sarah K.; Skoet, Jakob; Raney, Terri (World development, 2016)
•We estimate the number, size, and distribution of farms, and farmland worldwide.•Most of the world’s more than 570 million farms are small and family-run.•Small farms (less than 2ha) operate about 12% of the world’s agricultural land.•Family farms operate about 75% of the world’s agricultural land.•Continued efforts are needed to enhance agricultural census data. Numerous sources provide evidence of trends and patterns in average farm size and farmland distribution worldwide, but they often lack documentation, are in some cases out of date, and do not provide comprehensive global and comparative regional estimates. This article uses agricultural census data (provided at the country level in Web Appendix) to show that there are more than 570 million farms worldwide, most of which are small and family-operated. It shows that small farms (less than 2ha) operate about 12% and family farms about 75% of the world’s agricultural land. It shows that average farm size decreased in most low- and lower-middle-income countries for which data are available from 1960 to 2000, whereas average farm sizes increased from 1960 to 2000 in some upper-middle-income countries and in nearly all high-income countries for which we have information. Such estimates help inform agricultural development strategies, although the estimates are limited by the data available. Continued efforts to enhance the collection and dissemination of up-to date, comprehensive, and more standardized agricultural census data, including at the farm and national level, are essential to having a more representative picture of the number of farms, small farms, and family farms as well as changes in farm size and farmland distribution worldwide.